Collaborating with Rural Practice Patners to Address the Need for RNs in Primary Care - Robin Brown; Heidi Mennenga; Alham Abuatiq; Linda Burdette; Leann Horsley; Christina Plemmons (Rural Nurse Organization; Binghamton University, 2020)
Abstract Purpose: Primary care in rural areas of the U.S. urgently need competent healthcare providers, especially registered nurses (RNs). Registered nurses are ideal team members to help meet the primary care needs in rural communities, yet RNs are underutilized in primary care settings and rarely practice to the full scope of their license in these settings. The purpose of the project was to conduct a needs assessment with rural primary care practice partners to address the need for RNs in primary care. Sample: A needs assessment was sent to nurse leaders at 13 rural primary care facilities via an online survey in December 2018. Methods: This descriptive exploratory study utilized an online needs assessment survey to gather information from 13 rural clinical practice partners regarding their knowledge, interest, and use of RNs in primary care. Results: Twelve of the 13 rural clinical practice partners completed the needs assessment survey. A majority of the clinical partners indicated they felt knowledgeable about the RN full scope of license and expressed a high interest in the expanded role of the RN in primary care. The clinical practice partners reported interest in providing independent RN chronic and acute care visits, care management, medication management, and collaborative provider and RN visits. Conclusion: Conducting a needs assessment and collaborating with rural primary care practice partners to address the need for RNs in primary care is the first step in developing policies and utilizing RNs to the full scope of their license. Keywords: primary care, rural, registered nurses